Erosive potencial of energy drinks on the dentine surface - Pinto, Shelon Cristiina Souza [UNESP]; Bandeca, Matheus C; Silva, Carolina Naciben da [UNESP]; Cavassim, Rodrigo [UNESP]; Borges, Alvaro H; Sampaio, Jose Eduardo Cezar [UNESP] (Springer Nature, 2013)
Background: Considering the current high consumption of energy drinks, the aim of the present study is to evaluate the influence of energy drinks in removing the smear layer and exposing dentinal tubules on root surface. Methods: Dentine root surfaces were exposed using a diamond bur. Forty movements of scaling were performed in the area prepared in order to create a smear layer. One hundred and thirty specimens were obtained from 35 teeth. Specimens were randomly distributed into 12 groups (n = 10) and divided into subgroups according to the application: topical (n = 5) and friction (n = 5). Twelve energy drinks were evaluated: RedBull™, Burn™, TNT™, Flash Power™, Flying Horse™, Sports Drink™, Ionic™, Hot Power™, Army Power™, Gladiator™ and Bug™. Distilled water was used as a control group. The specimens were analysed by scanning electron microscopy. Results: Topical application: a significant influence of energy drinks on smear layer removal was found for FlyingHorse™ and Bug™ when compared with the control group. Friction application: significant smear layer removal was found for Burn™, FlyingHorse™, Gladiator™, SportsDrinks™, when compared with the control group. Comparing the different application forms, a statistically significant difference was found for Army Power™. Conclusion: Considering the significant smear layer removal, energy drinks can be an important etiological factor for cervical dentine hypersensitivity.
Keywords: Dentine hypersensitivity; Erosive tooth wear; Scanning electron microscopy; Dentinal tubules; Abrasion; Tooth wear; Root dentin; Toothbrushing